Economic Stability in Indonesia from an Islamic Perspective: A Systematic Literature Review (2015–2025) - Yovi Kusumadani; Ananto Triwibowo (Journal of Contemporary Applied Islamic Philanthropy, 2026)
Purpose: This study aims to analyse the concept of economic stability from an Islamic perspective using a Systematic Literature Review (SLR) approach. The study is motivated by the increasing global economic instability caused by inflation, financial crises, digital disruption and economic inequality, whilst research on Islamic economic stability remains largely fragmented and has yet to comprehensively integrate various Islamic economic instruments. Methodology: The research utilised the PRISMA methodology by reviewing nationally and internationally recognised scientific articles published between 2015 and 2025. Data were obtained from the Google Scholar, Scopus, and Science Direct databases using keywords related to economic stability, Islamic economics, and the Islamic financial system. Findings: The results indicate that economic stability from an Islamic perspective is not solely focused on economic growth but also emphasises aspects of distributive justice, social balance, sustainable welfare, and economic moral stability. Instruments such as zakat, waqf, Islamic banking and Islamic monetary policy make a significant contribution to maintaining the economic resilience of society. This study offers a conceptual contribution in the form of the integration of the principles of maqashid al-sharia and macroeconomic stability as an alternative model for a more inclusive and sustainable economy in the face of global economic uncertainty.